Academician Yuri Fedorovich Isakov (1923–2016) (on the 100th anniversary of his birth) - Al. A. Kurygin; V. V. Semenov; V. S. Dovganyuk (Вестник хирургии имени И.И. Грекова)
Outstanding pediatric surgeon, scientist, teacher and health care organizer, founder of a large school of pediatric surgeons, Honored Scientist of the RSFSR (1973), academician of the USSR Academy of Medical Sciences (1975) and the Russian Academy of Sciences (2013), vice-president of the Russian Academy of Medical Sciences (1989–2001), laureate of two State USSR Prizes (1979, 1985) and the State Prize of the Russian Federation (1999), Chief Pediatric Surgeon of the USSR Ministry of Health (1966–1981) and the Russian Ministry of Health (1992–2005), Deputy Minister of Health of the USSR (1981–1987), Professor Yuri Fedorovich Isakov was born on June28, 1923 in Kovrov, Vladimir region. In 1966, he was elected head of the department of surgical diseases of childhood at the 2nd Moscow Medical Institute named after N. I. Pirogov and led it for 40 years. The surgical and scientific activities of Yuri Fedorovich were distinguished by a very wide range of areas. On the problems of thoracic surgery, extensive experience has been accumulated in the treatment of children with diseases and malformations of the neck, chest, lungs, mediastinum, and esophagus. Many diverse research works have been carried out on topical issues of abdominal surgery. Yu. F. Isakov made a very large contribution to the development of endovideosurgery in children. The clinic became one of the first in the country to create a specialized endovideosurgical service. Under the leadership of Yuri Fedorovich and with his direct participation, pediatric nephrurology and vascular surgery quickly developed, scientific research was conducted on topical issues of combined trauma of the musculoskeletal system, an anesthesiology, resuscitation and intensive care service was organized in the clinic, fundamental research was carried out on the problem of pain management in children surgery. Yu. F. Isakov was the author and co-author of more than 500 scientific works, including 23 monographs and manuals, 7 textbooks and teaching aids. At the department headed by Yuri Fedorovich, 390 dissertations were defended, including 67 doctoral dissertations. Academician Yuri Fedorovich Isakov died on August 4, 2016 and was buried at the Troekurovskoye cemetery in Moscow.